The Adventures of Nosa the Supperhero - Martins, Sope (Nigeria, 2022)
Nosa has to learn how to fly like a superhero over the weekend or, on Monday, his friends will know he told a big, fat lie. He tries everything he can think of, but all that happens is his sister, Adesuwa, laughs at him. On Monday, Nosa will have to admit he can't fly, but not all superheroes need to fly!...
Keywords: Adventure; Juvenile Fiction